2009
DOI: 10.1590/s1413-70542009000100027
|View full text |Cite
|
Sign up to set email alerts
|

Características físico-químicas de amostras de méis de Apis mellifera L. do estado do Ceará, Brasil

Abstract: RESUMOObjetivou-se, na presente pesquisa, desenvolvida com amostras de méis de Apis mellifera coletadas diretamente dos produtores de diversos municípios do estado de Ceará, Brasil, verificar, com base em características físico-químicas, como se agrupam as amostras de méis. Dentre as 52 amostras de méis analisadas as que continham pólen de Serjania sp. como dominante ou acessório, formam um subgrupo distinto quanto aos caracteres físico-químicos, o que confirma que a origem floral interfere decisivamente nas c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
18

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 10 publications
1
10
0
18
Order By: Relevance
“…These values are close to those obtained by Komatsu et al (2002), Sodré et al (2002), Arruda et al (2005) and Moreti et al (2009), who found a variation from 67.8 to 88.3% in total sugar content of Brazilian honey samples obtained from different floral origins.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…These values are close to those obtained by Komatsu et al (2002), Sodré et al (2002), Arruda et al (2005) and Moreti et al (2009), who found a variation from 67.8 to 88.3% in total sugar content of Brazilian honey samples obtained from different floral origins.…”
Section: Resultssupporting
confidence: 91%
“…For Azeredo et al (1999), the high apparent sacarosis content in honey may be an indication of "unripe honey" due to its incomplete transformation into glucose and fructose by the action of the invertase enzyme secreted by bees, or due to honey adulteration. Moreti et al (2009) argue that sacarosis content slightly higher than the lower established value can be due to the fact that the bee collected feed from resources other than the nectar for that specific honey. The apparent sacarosis percentages obtained in our study are similar to those found by Baldi-Coronel et al (1993) in Argentina (1.00 to 13.00%) and by Vit-Oliver et al (1994) in Venezuela (1.74 to 11.99%).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…So far, there are relatively few researches about quality of honeys produced in the Northeast of Brazil, especially concerning honeys from specific floral species found in the Caatinga biome. Nevertheless, some authors have reported physicochemical characteristics of honeys from floral species of the Caatinga (Sodré et al 2007, Moreti et al 2009, Liberato et al 2013, Costa et al 2013. Studies on rheological behaviors of honeys, like other fluid foods, are important for applications related to handling, storage, processing, quality control, and sensory analysis (Yoo 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Por meio da diferença entre esses resultados, foi possível a obtenção dos teores de açúcares não-redutores (dissacarídeos). A porcentagem de inversão da sacarose foi obtida por meio da dosagem da sacarose, glicose e frutose, utilizando-se a equação (Rodrigues et al, 2000): açúcares redutores % inversão= x 100 açúcares redutores + 1,05 açúcares não-redutores Para critério de recomendação de limites inferior e superior da adição de ácido cítrico ou suco de limão, foi utilizado o intervalo de pH de méis citado por Marchini et al (2004) e Moreti et al (2009), visando a obtenção de uma dieta energética, para suplementação alimentar, com pH próximo àquele normalmente ingerido pelas abelhas africanizadas. Foi medido também o pH de amostras de méis obtidas, mensalmente, no apiário da UFLA no período de julho de 2007 a junho de 2008.…”
Section: Methodsunclassified